Molecular mechanisms of cryoablation-mediated lung cancer suppression unveiled by non-coding RNA regulatory network profiling - Xiaofan Wang; Mohan Zhang; Dianna Liu; Shicheng Lin; Yuxin Zhang; Quanwang Li (Scientific Reports)
Abstract While cryoablation demonstrates therapeutic potential for lung adenocarcinoma, the precise molecular mechanisms underlying its antitumor effects require further elucidation. We conducted the first transcriptome-based investigation of cryoablation’s anti-tumor mechanisms using the Lewis lung carcinoma (LLC) model. Subcutaneous LLC tumors were established in C57BL/6 mice, with subsequent randomization into the model, cryoablation, and cisplatin control groups (DDP). Systematic evaluations included the tumor volume and weight, histopathology (H&E staining), Ki-67 proliferative index (IHC). RNA sequencing identified differentially expressed genes (DEGs), and bioinformatics analysis constructed lncRNA/miRNA-mRNA regulatory networks, with key targets validated by RT-qPCR and Western blotting. Our findings revealed that cryoablation significantly inhibited tumor growth (volume/weight reduction) and downregulated the Ki-67 proliferative index. Transcriptomic profiling identified 1136 mRNA, 215 lncRNA, and 39 miRNA DEGs, unveiling critical PDK1-VEGFA axis regulation and mmu-miR-210-5p-ANKFY1 targeting. Western blot analysis confirmed that cryoablation blocked the HIF-1 signaling pathway by inhibiting HIF-1α and VEGF protein expression. This study elucidates that cryoablation exerts anti-tumor effects via HIF-1 pathway blockade and non-coding RNA network remodeling, providing a theoretical foundation for optimizing cryotherapeutic strategies.